SELF EFFICARY DAN KINERJA INDIVIDUAL - SUKRISPIYANTO (AKADEMIKA, 2018)
Self-efficacy is a person's belief in his chances of successfully achieving a particular task. Self-efficacy is a personal factor that distinguishes each individual. Changes in employee self-efficacy can cause behavior changes, especially in the completion of tasks and goals. Employees who have high self-efficacy, will devote all their effort and attention in accordance with the demands of the situation, to achieve the goals and performance that has been set. Failure to achieve the goal makes employees work harder to achieve it again, overcome obstacles that make it fail, and after successfully overcoming it the employee will re-assign another higher target. Trust in one's ability, confidence in success achieved by all means making someone work harder and produce the best. This paper aims to explain the relationship between self-efficacy and individual performance in terms of theoretical aspects and empirical approaches.